(untitled) (Journal of Medicine, 2014)
Laurence-Moon-Bardet-Biedl syndrome is a rare autosomal recessive disorder characterized bystructural and functional abnormalities of different organ and tissues. Renal involvement is the single most feature of prognostic importance. We report a case with end stage kidney disease. The diagnosis was missed until patient presented with renal dysfunction. Early diagnosis and screening for renal involvement is crucial for prolong survival. DOI: http://dx.doi.org/10.3329/jom.v15i1.19885 J Medicine 2014; 15: 94-97